Fixation of tibial plateau fracture – risk factors for developing infection: a narrative review - Nicolas Franulic; Jose Tomas Muñoz; Tomas Pineda; Jose Laso; Rodrigo Olivieri; Steffen Schröter (EFORT Open Reviews)
Fracture-related infection (FRI) after tibial plateau open reduction and fixation is a common complication that leads to catastrophic sequelae and substantial economic costs, making prevention paramount. To facilitate an appropriate approach, it is useful to classify risk factors based on patient-related factors, injury-related factors, and management-related factors. Patient-related factors like smoking have a great amount of evidence establishing their relation with FRI. Diabetes and obesity might be associated, but evidence is somewhat conflicting. Nevertheless, smoking cessation and a multidisciplinary approach for these pathologies are essential to prevent FRI. Injury-related factors like high-energy fractures and acute compartment syndrome have compelling evidence relating them to FRI and must be acknowledged as inherent factors. While the exposure of the fracture has been associated with infection, open fractures are yet to be confirmed as directly related to FRI in tibial plateau fractures. Likewise, early antibiotic prophylaxis and surgical debridement are mandatory. As for management-related factors, increased surgical time emerges as a strong predictor for FRI. Evidence regarding the number of surgical approaches and plates shows a trend toward an increase in FRI prevalence. With respect to external fixator installation and removal, pin-plate overlapping is yet to be confirmed or ruled out as risk factors.